Traditional literacy skills and internet use among 8 to 12 year old children - Johnson, Genevieve (Routledge Taylor & Francis Group, 2013)
Ninety children in third through sixth grade attending an elementary school in western Canada completed a 15-item rating scale of their Internet use across home, school, and community contexts. Children's literacy skills were assessed with standardized measures of reading fluency and sentence comprehension and teacher ratings of reading and writing ability. Results suggest that Internet use during childhood is a complex behavior that varies across children and across contexts. Instant messaging and community-based Internet use during childhood were associated with decreased literacy skills, while other applications used at home and school were associated with increased literacy skills.